2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7319284
|View full text |Cite
|
Sign up to set email alerts
|

Source-domain spectral EEG analysis of sports-related concussion via Measure Projection Analysis

Abstract: Here, we investigated EEG-based source-level spectral differences between adolescents with sports-related concussions and healthy age matched controls. We transformed resting state EEG collected in both groups to the source domain using Independent Component Analysis (ICA) and computed the component process power spectra. For group-level analysis in the source domain, we used a probabilistic framework, Measure Projection Analysis (MPA), that has advantages over parametric k-means clustering of brain sources. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…In a cross-sectional study utilizing resting-state EEG, the British Columbia group (Balkan et al, 2015; Virji-Babul et al, 2014) reported increased beta, reduced theta, and reduced delta power across several frontal sources for SRC patients relative to uninjured control athletes, as well as abnormal connectivity metrics. In a study with overlapping samples, the Belgium group (van Beek et al, 2015a) utilized EEG to demonstrate that pmTBI patients exhibited lower amplitude in a late positivity component (posited to reflect attentional failure) during cognitive tasks, but were similar across more basic early sensory components.…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…In a cross-sectional study utilizing resting-state EEG, the British Columbia group (Balkan et al, 2015; Virji-Babul et al, 2014) reported increased beta, reduced theta, and reduced delta power across several frontal sources for SRC patients relative to uninjured control athletes, as well as abnormal connectivity metrics. In a study with overlapping samples, the Belgium group (van Beek et al, 2015a) utilized EEG to demonstrate that pmTBI patients exhibited lower amplitude in a late positivity component (posited to reflect attentional failure) during cognitive tasks, but were similar across more basic early sensory components.…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…EEG spectral differences have been used to differentiate matched controls from those with pathological conditions like dyslexia (Galin et al, 1992;Papagiannopoulou and Lagopoulos, 2016), insomnia (Buysse et al, 2008), fibromyalgia (Gonzalez-Roldan et al, 2016), epilepsy (Adebimpe et al, 2015), adolescents with sports related concussions (Balkan et al, 2015), and Parkinson’s disease (Caviness et al, 2016). In the current study, μ-β amplitudes did not correlate with a behavioral measure of stuttering severity making it unclear how well μ-β amplitude defines the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…oscillations with frequencies down to ∼ 0.01 − 0.02 Hz (also known as infraslow oscillations or ISO). The latter was motivated by two considerations: (a) EEG studies find that, compared to healthy controls, concussed athletes exhibit altered activity in the delta band (0.5 − 4 Hz) [19,33,89], with increasing divergences towards to lowest frequencies. (b) Among adolescents, one of the resting state networks strongly impacted by concussion is the default mode network (DMN) [20,48].…”
Section: Data Segmentation and Augmentationmentioning
confidence: 99%
“…At the group-level, structural changes in the integrity of white matter in adolescents has been observed using diffusion tensor imaging (DTI) [20,[27][28][29][30][31][32]. Similarly, studies of youths during "resting state" reveal significant mTBI-induced alterations in the functional organization of the brain with respect to their healthy counterparts, with key features being (i) a shift in spectral profile toward higher frequencies in the frontal brain regions, [33] (ii) an increase in functional connectivity (hyperconnectivity) [17,34,35], and (iii) disrupted information flow patterns [24], again particularly in the frontal regions. All of these studies rely on summary measures to characterize functional changes in the brain.…”
Section: Introductionmentioning
confidence: 99%